2022
DOI: 10.3390/met12061008
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a Rough Surface with Submicron Ti2Cu Particle on Ti-Cu Alloy and Its Effect on the Antibacterial Properties and Cell Biocompatibility

Abstract: Titanium-copper (Ti-Cu) alloy is an advanced antibacterial material with excellent mechanical properties, thermodynamic stability, corrosion resistance and biocompatibility. Sandblasting and acid-etching was applied to the Ti-3Cu alloy to construct a rough surface with Ti2Cu phase on the surface in order to improve the antibacterial properties and the osseointegration. The phase constitutes and the physical properties were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM) and confoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Moreover, Xie et al. [ 237 ] confirmed that the existence of MAPD between Ti 2 Cu and the matrix results in the antibacterial effect of the Ti–Cu alloy. Thus, the formation of Ti 2 Cu phase plays a pivotal role in the antibacterial behavior of Ti–Cu alloys [ 238 ].…”
Section: Ti–cu Antibacterial Implantsmentioning
confidence: 99%
“…Moreover, Xie et al. [ 237 ] confirmed that the existence of MAPD between Ti 2 Cu and the matrix results in the antibacterial effect of the Ti–Cu alloy. Thus, the formation of Ti 2 Cu phase plays a pivotal role in the antibacterial behavior of Ti–Cu alloys [ 238 ].…”
Section: Ti–cu Antibacterial Implantsmentioning
confidence: 99%
“…For example, in order to improve the interface bonding strength of the dental implant and bone tissue, a rough surface was produced on the surface of the dental implant by means of SLA [26], the selective etching process [9], etc. It was reported the surface roughness should be 1.5 µm to 2.5 µm in order to obtain satisfactory bonding strength [27,28]. It has also been shown that titanium oxide (TiO 2 ) films grown spontaneously on the surface of titanium alloys are bioinert, often leading to inadequate bone integration [29][30][31].…”
Section: Surface Morphology and Chemical Compositionmentioning
confidence: 99%
“…Nevertheless, Ti64 alloy shows serious drawbacks such as poor wear resistance and low antibacterial activity, which may result in the early degradation of long-term prostheses [3]. To overcome these drawbacks, the addition of antibacterial metals such as silver and copper has been proposed [4][5][6][7][8][9][10][11][12]. It has been reported in [13,14] that a high level of antibacterial activity is reached with the addition of less than 5 wt% of Cu or Ag.…”
Section: Introductionmentioning
confidence: 99%